Hydrogen-oxygen mixture inhalation as an adjunctive treatment to home-based exercise in older patients with knee osteoarthritis: an open-label, blinded-endpoint, randomized controlled trial - Wang, Chenhui; Yan, Mengwei; Li, Yuru; Han, Lei; Wang, Hongqian; Jia, Shufeng; Liu, Xingchen; Liu, Yang; Wu, Fan; Wang, Baoguo (Frontiers in Pharmacology, 2025)
ObjectiveKnee osteoarthritis (KOA) is a degenerative joint condition, leading to disability and diminished quality of life. Molecular hydrogen has been proven to have antioxidant and anti-inflammatory properties, but few studies have investigated its effects on osteoarthritis. Our study aims to assess the therapeutic potential of hydrogen-oxygen mixture (H2-O2) inhalation for KOA.MethodsIn this randomized controlled trial, eligible elderly KOA patients were randomly assigned to either Group H or Group C. Both groups participated in a 12-week home-based exercise (HBE) program, which included knee-joint exercises and health education. Group H additionally received H2-O2 inhalation for 60 min per day over 2 weeks, while Group C did not. The primary outcome was measured using Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Secondary outcomes included inflammation levels (hs-CRP, NLR, PLR, LMR), Chair Stand Test (CST), Timed Up and Go (TUG), 36-item short-form health survey (SF-36), Exercise Adherence Rating Scale (EARS), and adverse events.ResultsA total of 121 subjects were enrolled, with an average age of 81.2 years, and 80.2% were female. The between-group mean difference in the WOMAC total score was −5.2 (95% CI −12.1 to 1.7, P = 0.140) at week 12, with Group H showing an improvement of −22.9 (95% CI −26.3 to −19.6, P < 0.001) and Group C showing an improvement of −19.4 (95% CI −22.7 to −16.0, P < 0.001) compared to baseline, revealing a significant group × time interaction (F (3, 356.034) = 14.425, P < 0.001). No significant differences were observed between both groups at week 12 in CST, TUG, SF-36 scores, EARS scores, or the incidence of adverse events.ConclusionAlthough clinical significance was not achieved, H2-O2 inhalation alleviated KOA symptoms and enhanced functional activity in elderly patients undergoing the HBE program during the initial 2 weeks. However, its sustained effects on improving KOA symptoms were not observed.